An experimental study on bidirectional pedestrian flow involving individuals with simulated disabilities in a corridor. (June 2022) - Fu, Libi; Liu, Yuxing; Qin, Huigui; Shi, Qingxin; Zhang, Ying; Shi, Yongqian; Lo, Jacqueline T.Y.
Highlights: A controlled experiment was conducted to explore dynamics of heterogeneous crowds in counter flow. The avoidance effect is more evident in minor flow. Helping behavior has a positive effect on movement efficiency of heterogeneous crowds. The proportion of individuals with simulated disabilities has a negative impact on counter flow. Congestion level is higher here than that in counterflow including all individuals without disabilities. Abstract: Individuals with disabilities are essential members of heterogeneous crowds. However, empirical data on pedestrian flow, including individuals with disabilities, are limited. In this study, a controlled experiment was conducted to explore the dynamics of counterflow involving individuals without disabilities and with simulated disabilities. For safety reasons, some individuals without disabilities were recruited to simulate persons with mobility-related physical and sensory disabilities (namely pedestrians on crutches, seniors, wheelchair users and persons who are blind) by using auxiliary equipment. A total of 64 pedestrians participated in the experiment. After gaining their movement trajectories, crossing behaviors, spatial–temporal characteristics, fundamental diagrams and the congestion level are analyzed under different split flow ratios of walkers from two directions and densities. Results demonstrate that the average speed of pedestrians in the direction of pedestrian flow comprising more participants is higher than that in the other direction. Helping behavior positively impacts on the movement efficiency of heterogeneous crowds, while the proportion of individuals with simulated disabilities has a negative impact. The split flow ratio has little effect on the average specific flow when density is smaller than approximately 1.25 m −2 . The average specific flow in balanced flow (i.e. the split flow ratio is 0.5) is slightly higher than that in unbalanced flow (i.e. the split flow ratio is not 0.5) when density is larger than approximately 1.25 m −2 . Congestion level is relatively higher here than that in counterflow, including all individuals without disabilities, when density is low. These findings have implications for safer pedestrian facility design.